Practice-Driven Research on Enterprise Transformation 6th Working Conference, PRET 2013, Utrecht, The Netherlands, June 6, 2013. Proceedings - Harmsen, Frank; Proper, Henderik A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume constitutes the proceedings of the 6th Working Conference on Practice-Driven Research on Enterprise Transformation (PRET), held in Utrecht, The Netherlands, on June 6, 2013, co-located with the Enterprise Transformation Track of the 21st European Conference on Information Systems (ECIS). Successful enterprises have well-defined managerial responsibilities and understandable project priorities and enable their processes to be sufficiently agile, even improvisational and continuously changing. They do not solely rely on only mechanistic or purely organic processes and structures, but see enterprise transformation as a combination of deliberate and organic change. This year's papers represent this hybrid view. Moreover, most of them are based on practical cases, which will further contribute to our understanding of enterprise transformation. The eight papers presented in this volume were allocated to tracks on: practical experiences with methods and techniques; cases in enterprise transformation; and enterprise architecture in practice.
Practical Experiences with Methods and Techniques -- Cases in Enterprise Transformation -- Enterprise Architecture in Practice.
Keywords: Economics; Information systems; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems